Restaurant Choice Intention in Kathmandu: The Roles of Endorser Trustworthiness and Likability - Janga Bahadur Hamal; Narayan Prasad Aryal; Chhemanand Joshi; Gobind Kumar Singh (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
The study purposes to investigate the impact of the Instagram micro-influencers on restaurant choice intention among the social media users in the capital city of Nepal, Kathmandu. The study employed an explanatory research design using the cross-sectional survey data that was administered to 332 Instagram users who follow at least one food related content creator. The endorser trustworthiness and endorser likability were used as antecedents of restaurant choice intention. The variables were measured using a five-point Likert instrument. Descriptive and inferential statistical tools were used for describing the nature of data and establishing relationships as well as examining the impact through ordinary least squares regression model respectively. The findings showed that both trustworthiness and likability are positively correlated with restaurant choice intention among the respondents. Moreover, trustworthiness plays the most important role in choosing the restaurants for food whereas both the antecedents have positive and significant impact on restaurant choice intention. The study depicted that the creators perceived as dependable, sincere, friendly, and honest are more likely to convert exposure into choice intention of restaurants for the Instagram users. The empirical evidence from Kathmandu based consumers influenced by micro-influencers, particularly Instagram, contributes to the corpus by modelling choice intention of restaurants as outcome. The insights of the study emphasize that the managers could select the content creators prioritizing the credibility and honesty to enhance the business of the restaurants. Such marketing contents could strengthen credibility and social connection which could convert online engagement to restaurant choice decision for dining. However, the study’s cross-sectional and self-reported data by the respondents of Kathmandu only might limit the causal inference and overall generalizability. Therefore, future research might be conducted covering the broader scope in terms of determining factors, demography, and sample size employing behavioral factors as mediators or moderators.